Impact of Autoimmune Thyroiditis on Reproductive and Metabolic Parameters in Patients with Polycystic Ovary Syndrome - Ulrich, Jan; Goerges, Julia; Keck, Christoph; Müller-Wieland, Dirk; Diederich, Sven; Janssen, Onno Eilard (Experimental and Clinical Endocrinology & Diabetes, 2018)
Background Autoimmune thyroiditis (AIT) has been found to be associated with polycystic ovary syndrome (PCOS). The aim of this retrospective cohort study using data from a fertility clinic, with patients recruited from 2009 to 2010, was to confirm the higher prevalence of AIT in PCOS and to evaluate the impact of AIT on reproductive and metabolic parameters of PCOS patients.Methods Patients comprised 827 PCOS subjects seen for reproductive or metabolic complaints. Patients presenting primarily for thyroid problems were excluded. All patients were tested for the presence of AIT by laboratory testing and thyroid ultrasound. The impact of AIT on PCOS was evaluated by determination of reproductive and metabolic parameters.Results Patients with PCOS and AIT as compared to those only with PCOS, had a lower prevalence of elevated testosterone (45 vs. 61%; p=0,0001), free androgen index (5,96±5,41 vs. 7,02±7,6; p<0,001) and hyperandrogenemia (66 vs. 78%; p<0,001). Also testosterone levels were lower in PCOS patients with AIT (0,50±0,30 vs. 0,63±0,71; p=0,0006). Consequently, in these patients, hirsutism was less frequent (51 vs. 66%; p=0,0021). There was no difference in the prevalence of acne, alopecia, a-/ or oligomenorrhea or PCO-morphology in the two patient groups. Patients with PCOS and AIT were more obese by 2 kg/m² BMI on average. A higher BMI correlated with a higher TSH value, although all patients were euthyroid.Conclusions AIT is more prevalent in PCOS than in controls. PCOS patients with AIT have less severe hyperandrogenemia and hyperandrogenism but are likely to suffer from an elevated metabolic risk.
Keywords: Polycystic ovary syndrome; PCOS; Autoimmune thyroiditis; AIT; Metabolic syndrome; Obesity; Hyperandrogenemia; Hyperandrogenism